IMPLEMENTASI STRATEGI PEMSARAN PADA BIRO PERJALANAN UMRAH DALAM PERSPEKTIF PEMASARAN SYARIAH - Nurfauzia, Vira; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2020)
The increase in Hajj registrants in Indonesia every year causes the pilgrimage queue to be longer which makes opportunities for Hajj and Umrah travel. However, there are some companies that are less responsible in conducting their business, so that makes some people lack trust in the Hajj and Umrah travel. This study aims to know the marketing strategy aplication of Umrah Travel Agency based on the perspective of sharia marketing. This marketing strategy needs to be carried out in order to increase the trust of prospective customers. The marketing strategies used in this research are the marketing mix of 9p + c (product, price, place, promotion, people, process, physical evidence, promise, patience, customer centrism). This study uses a descriptive qualitative approach with the case study method at PT. Nur Dhuha Wisata in Surabaya. The technique of data collecting uses interview, observation, and documentation. Based on the results of the study, the implementation of the marketing strategy undertaken by PT. Nur Dhuha Wisata has been appropriate with the principles of sharia marketing which consists of the principle of monotheism or piety, the principle of human unity or justice, and the principle of belief in the unity of the world and the hereafter.